Historical heritage of the lower valley of the Chillón River. Heritage Research and Education - Cabanillas Delgadillo, Virgilio Freddy (2023)
This article examines approaches the cultural heritage characteristics of the Lower Chillón River Valley populations, from a multidisciplinary perspective: archaeology, history, architecture and education. In order to accomplish such goal, it is discussed the history and current state of the Pre-Hispanic, Colonial and Republican cultural legacy of the studied area, along with its conservation and implementation of educational programs for the local community.